Does Meaning Motivate Magical Thinking Among Theists and Atheists?. Issue 2 (March 2020) - Nelson, Taylor A.; Abeyta, Andrew A.; Routledge, Clay
Past research indicates that existential threats related to meaning in life increase religious-related magical beliefs (e.g., belief in God). The present three studies examined more broadly whether threatened meaning influences magical ideation and beliefs among atheists and theists. Amazon Mechanical Turk ( N = 1, 454) and student participants ( N = 50) were randomly assigned to a meaning threat or control condition and then completed measures of magical ideation and beliefs. Across three studies ( N = 1, 504), we did not find experimental evidence that threatened meaning increases magical ideation and beliefs. However, in Study 3, we also examined the link between the meaning motive and magical ideation and beliefs using an individual difference approach and found that the need for meaning was a significant predictor of magical ideation and beliefs, particularly among atheists.